The Divergence Between Prophet’s Masjid and Present Masjid: An Architectural Essay - Deni, Deni; Karsono, Bambang; Mirsa, Rinaldi; Safyan, Adi; Saputra, Eri (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Basically, functional aspect in masjid can easily understand that there are divergence phenomena between the present masjid compared to the physical appearance and function of the Prophet's Masjid in the beginning. The objective of study is to reveals the existence of the Prophet's Masjid regarding the process and physical description of the masjid through hadith, sirah nabawiyah and related references as a guideline for comparative thinking on the present masjid. Critical descriptive research method is used as an analytical instrument to assess present masjid by adopting the idea of function in architecture knowledge and collaborate with the idea of social values as a reflection of the paradigm of Muslims towards the present masjid. Discussion find out that the people's perspective on present masjid tends to be statically trapped in the shape, form and visuals from the legacy of Islamic civilization after the time of the Prophet’s Muhammad PBUH.